Going into the Field: The Sensory Experience of Design Students on Spatial Atmosphere of Art Fashion Retail - Eri Naharani Ustazah; Purwanita Setijanti; Arina Hayati (Jurnal Pendidikan: Teori, Penelitian, dan Pengembangan, 2023)
Today's retail architecture is developed by creating experiences, sensory experience is one of its aspects. Design students are expected to understand the concept, so this study aims to explore the sensory experience of students in a special retail space, namely art fashion retail. This research uses the qualitative photo elicitation method, participants are brought into real retail space and follow-up interviews are accompanied by photos. The findings revealed that only a small of participants paid attention to both tangible and intangible elements. So, for further assessment, it is necessary to match knowledge between education and the real world